MyPTJobs: My Part Time Jobs Mobile Application - Er, Wang Xing; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2023)
Part-time work is a popular and flexible option for many individuals in Malaysia but finding suitable opportunities can be challenging. Traditional methods such as visiting businesses in person or browsing job postings on social media are time-consuming and may not be reliable. In response to these issues, this project proposes the development of an application that connects job seekers with part-time employment opportunities in Malaysia. Prototyping-based methodology is used as the methodology to execute the project and the application and is developed in Android platform by using Flutter, Java and MySQL. MyPTJobs provides a convenient and efficient way for job seekers to find suitable jobs, while also helping employers to find additional staff on a part-time basis. Based on functional testing, it is shown that all the requirements have been successfully fulfilled and has streamlined the job search process and provide a valuable resource for both job seekers and employers.